Blood cell count in antipsychotic‐naive patients with non‐affective psychosis. Issue 1 (8th August 2017) - Garcia‐Rizo, Clemente; Casanovas, Marta; Fernandez‐Egea, Emilio; Oliveira, Cristina; Meseguer, Ana; Cabrera, Bibiana; Mezquida, Gisela; Bioque, Miquel; Kirkpatrick, Brian; Bernardo, Miquel
Abstract : Background: Schizophrenia is a complex medical entity with a reduced life expectancy, mostly due to an increased prevalence of cardiovascular diseases compared to the general population. An unbalanced immune response and a pro‐inflammatory state might underlie this process. In treated patients, abnormal white blood cell (WBC), lymphocyte and neutrophil count suggests atypical immune response related to clinical variables. We aimed to test the hypothesis that newly diagnosed naïve patients with non‐affective psychosis would show abnormal blood cell count values after controlling for potential confounding factors compared to matched controls. Methods: Seventy‐five patients were compared with 80 controls matched for age, gender, body mass index and smoking. Analyses were conducted before and after controlling for smoking. Results: Patients and controls displayed similar mean values (×10 3 /μL [SD]) for WBC count 7.02 [2.2] vs 6.50 [1.7] ( P = .159), neutrophil count 4.25 [1.8] vs 3.84 [1.3] ( P = .110) and monocyte count 0.43 [0.2] vs 0.40 [0.1] ( P = .326). After controlling for smoking, 38 non‐smoking patients showed a higher WBC and neutrophil count compared with 49 matched controls. Respective means of 7.01 [2.2] vs 5.97 [1.4] ( P = .011) for WBC and 4.24 [1.9] vs 3.51 [1.2] ( P = .028) for neutrophil count. Monocyte count showed an increased mean value 0.43 [0.2] vs 0.36 [0.1] with a trend towards signification ( P = .063). Conclusions: These results suggest that abnormal immune response is present before the effects of medication and other confounders had taken place. Increased immune parameters might underlie the high ratio of medical co‐morbidities described in schizophrenia.